The facts of life [videorecording (DVD)] - Frank, Melvin, 1913-1988; Hope, Bob, 1903-2003; Ball, Lucille, 1911-1989; Defore, Don, 1913-1993 (Olive Films, 2015)
When their spouses are unable to join them on a planned group trip, longtime friends, Larry Gilbert and Kitty Weaver find themselves thrown together and falling in love under the sun in beautiful Acapulco. With their vacation coming to an end, both Larry and Kitty find themselves torn between feeling guilty about the affair and whether or not to end it.